Cocaine Directly Impairs Memory Extinction and Alters Brain DNA Methylation Dynamics in Honey Bees - Søvik, Eirik; Berthier, Pauline; Klare, William P.; Helliwell, Paul; Buckle, Edwina L. S.; Plath, Jenny A.; Barron, Andrew B.; Maleszka, Ryszard (Frontiers in Physiology, 2018)
Drug addiction is a chronic relapsing behavioural disorder. The high relapse rate has often been attributed to the perseverance of drug-associated memories due to high incentive salience of stimuli learnt under the influence of drugs. Drug addiction has also been interpreted as a memory disorder since drug associated memories are unusually enduring and some drugs, such as cocaine, interfere with neuroepigenetic machinery known to be involved in memory processing. Here we examined whether or not cocaine affects memory processing independently of its effect on incentive salience. Using the honey bee (an established invertebrate model for epigenomics and behavioural studies) we isolated the direct effects of cocaine on learning and memory processing from any effects of cocaine on incentive salience. We found that cocaine strongly impairs consolidation of extinction memory, and that this can be correlated to the effects of cocaine on epigenetic processes. In bees cocaine directly inhibits the extinction of memory independently of any effects on incentive salience. These findings emphasise the impact of cocaine on memory systems, with relevance for understanding how cocaine can have such an enduring impact on behaviour.